Aplikasi sistem Pencatatan Kreatif Siswa Berbasis Desktop Pada SMK N 9 Medan - Hafni; Irwan (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
The ability to think creatively is the ability of students to find solutions that are unusual, unique and have never been found by others. The purpose of this study was to determine the level of creative thinking skills possessed by students. The approach to this study uses the Simple Additive Weighting (SAW) method, often also known as the weighted sum method. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The results of this study show that students can be divided into 2 parts of creative students, namely creative students are accepted and students who are not creative are not accepted. Data collection is done by providing creative types that have been done by students and includes indicators of creative thinking skills, namely fluency, flexibility, originality and elaboration. In this study, it was found that 5 students had a very creative thinking ability, 1 student had a creative thinking ability and 1 student had a low creative thinking ability.